Stories of magical animals - Watson, Carol (Usborne London, 2007)
The two popular titles in "Usborne Young Reading Series One" have been re-issued in luxurious hardback editions with ribbon markers. The desirable and collectable editions help to foster pride in book ownership as well as reading enjoyment. "Young Reading Series One" is aimed at children just beginning to read to help build confidence and ability. It is developed in consultation with Alison Kelly, who is a senior lecturer in education and an early reading specialist from Roehampton University.